PRODUCTIVITY VIEWED FROM ORGANIZATIONAL DEVELOPMENT, COMMITMENT, AND WORK CULTURE IN HEALTH HIGHER EDUCATION - Damayanti, Pamela; Askafi, Eka; Mulyaningtiyas, Ratna Dewi (Jurnal Apresiasi Ekonomi, 2023)
The purpose of this study was to analyze the effect of organizational development, commitment and work culture toward the work productivity of the employees of the STRADA Indonesia - Institute of Health Sciences. The research method used in this research is descriptive method with a quantitative approach. The location of the research was carried out at the STRADA Indonesia - Institute of Health Sciences (IIK) with 61 lecturers and education staff as the respondents. The instrument used is a questionnaire regarding organizational development, commitment, culture and employee’s work productivity. The results of this study indicated that both partially and simultaneously organizational development, commitment and work culture affected the work productivity of STRADA Indonesia - Institute of Health Sciences employees. And the most dominant effect on productivity was work culture, which meant that a positive work habits that grew in the organization had to be maintained in order to continue to increase employee’s work productivity at the STRADA Indonesia - Institute of Health Sciences (IIK).